Explode every day an inquiry into the phenomena of wonder - Markonish, Denise (DelMonico Books, Prestel, 2016)
Inspired by a quote from Ray Bradbury, "Explode Every Day" is a bold new exhibition harnessing the energy of wonder. This book features works touching on certain facets of wonder, including themes of the perceptual/visionary, technological/scientific, and time/cosmos. In compelling essays on the history of wonder and its intersection with myriad disciplines, including psychology, literature, and science, today’s great minds consider the many avenues for this phenomena. Interviews with the exhibition’s artists provide insight into individual processes of creativity and innovation. The result is an awe-inspiring exploration of the richness of wonder: from the every day to the ineffable. - Published to accompany the exhibition held at MASS MoCA, North Adams, Massachusetts, 28th May 2016 - March 2017
Keywords: Art, American / 21st century / Exhibitions; Wonder; Awe; Curiosity; Wunder -- Motiv; Ausstellungskatalog; Ausstellungskatalog -- Massachusetts Museum of Contemporary Art -- 28.05.2016-02.04.2017 -- North Adams, Mass.